2006-06-18
展开全部
解:首先化简m-2(n-1)=0
3m-3(n-2)=1
得 m-2n=-2 ① (设①式,②式)
3m-3n=-5 ②
①式×3-②式
得 (m×3-3m)+(-2n×3-(-3n×3))=-2×3-(-5)
即 -3n=-1
n=1/3 ③
将③代入①得
m-2×1/3=-2
m=-4/3
所以 m=-4/3
n=1/3
3m-3(n-2)=1
得 m-2n=-2 ① (设①式,②式)
3m-3n=-5 ②
①式×3-②式
得 (m×3-3m)+(-2n×3-(-3n×3))=-2×3-(-5)
即 -3n=-1
n=1/3 ③
将③代入①得
m-2×1/3=-2
m=-4/3
所以 m=-4/3
n=1/3
展开全部
拆开
m-2n+2=0 (1)
3m-3n+6=1 (2)
(1)乘以3,得 3m-6n+6=0
(2)-(1)得
3n=1
n=1/3
将n代入(1),得出m=-4/3
自行检验
m-2n+2=0 (1)
3m-3n+6=1 (2)
(1)乘以3,得 3m-6n+6=0
(2)-(1)得
3n=1
n=1/3
将n代入(1),得出m=-4/3
自行检验
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
m-2n+2=0
m-2n=-2 (1)
3m-3n+6=1
3m-3n=-5 (2)
(1)*3,
3m-6n=-6 (3)
(2)-(3),
3n=1
n=1/3
把代入(2)
3m-1=-5
3m=-4
m=-3/4
m-2n=-2 (1)
3m-3n+6=1
3m-3n=-5 (2)
(1)*3,
3m-6n=-6 (3)
(2)-(3),
3n=1
n=1/3
把代入(2)
3m-1=-5
3m=-4
m=-3/4
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
可以转化为:
M=2N-2(1)
3M=3N+6(2)
将(2)除以3,得:
M=N-3,最后得:2N-2=N+2
解得:N=4,M=6.
谢谢采纳!
M=2N-2(1)
3M=3N+6(2)
将(2)除以3,得:
M=N-3,最后得:2N-2=N+2
解得:N=4,M=6.
谢谢采纳!
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询